Reproducibility of Bacterial Cellulose Nanofibers Over Sub-Cultured Generations for the Development of Novel Textiles - Wood, Jane; van der Gast, Christopher; Rivett, Damian; Verran, Joanna; Redfern, James (Frontiers in Bioengineering and Biotechnology, 2022)
The textile industry is in crisis and under pressure to minimise environmental impact in its practices. Bacterial cellulose (BC), a naturally occurring form of cellulose, displays superior properties to that of its cotton plant counterpart, such as enhanced purity, crystallinity, tensile strength, and water retention and thus is suitable for an array of textile applications. It is synthesised from a variety of microorganisms but is produced in most abundance by Komagataeibacter xylinus. K. xylinus is available as a type strain culture and exists in the microbial consortium commonly known as Kombucha. Whilst existing literature have described the effectiveness of both K. xylinus isolates and Kombucha in the production of BC this study investigated the change in microbial communities across several generations of subculturing and the impact of these on BC yield. Using Kombucha and single isolate strain K. xylinus as inocula in Hestrin and Schramm liquid growth media, BC pellicles were propagated. The resulting pellicles and residual liquid media were used to further inoculate fresh liquid media and this process repeated over three generations. For each generation, the thickness of the pellicles and their appearance under SEM was recorded. 16S rRNA sequencing was conducted on both pellicle and liquid media samples to assess changes in communities. The results indicated that the genus Komagataeibacter was the most abundant species in all samples. Cultures seeded with Kombucha yielded thicker cellulose pellicles than those seeded with K. xylinus, but all the pellicles had similar nanofibrillar structures, with a mix of liquid and pellicle inocula producing the best yield of BC after three generations of sub culturing. Therefore, Kombucha starter cultures produce BC pellicles which are more reproducible across generations than those created from pure isolates of K. xylinus and could provide a reproducible sustainable model for generating textile materials.